Management of Principles in Improving the Quality of Teachers in Sekolah Penggerak in the City of Samarinda - Syafrudin Januar; Rahmad Soe’oed; Laili Komariyah (PT ARRUS Intelektual Indonesia, 2022)
The purpose of this study is to describe the management of school principals in improving the quality of teachers in sekolah penggerak, which will specifically look at how the planning by principals in sekolah penggerak at every level, namely by looking at comparisons at each level. levels, namely Elementary School Level, Junior High School Level and High School Level which have been appointed as the driving school for Batch 1 in Samarinda City. This research uses a qualitative approach with a case study method, and the subject of this research is the principal. Data were collected by interview, observation, and documentation. With informants in each school consisting of three people, the principal as a key informant, then two other informants namely the Deputy Principal and the teacher. Data validity was obtained by using data triangulation, namely source triangulation and technical triangulation at each school level studied. The data analysis method used is interactive data analysis developed by Miles & Huberman which consists of data reduction, display, and verification or drawing conclusions. The results of this study are that the principal's management in improving the quality of teachers in driving schools at different levels has similarities.